Role of Physics in Engineering Education - Rao, A. P. (Journal of Engineering Education Transformations, 1994)
This short paper initially deals with the explanation of the science as the attempt to investigate and understand the mystery of the nature as perceived by our senses and experience in replicable manner that corresponds to a logically uniform system of thought and engineering as the application of science in economically acceptable form. And, therefore, basic sciences have their own importance in the broad spectra of engineering education system. The history of physics and its relation with engineering have been discussed. Then our present engineering education system and the status provided to the subject physics have been discussed. The need is to frame the syllabus in proper way for various engineering courses with logical step-up. The author stresses on a multi-tier changes in the structure of current curricula to start constructive interaction between physicist and engineers of the future, right from degree level. From author's point of view, the coordination among physicists, engineers and educationists shall help the engineering students to go for higher studies which positively affect our technological development. Then,. the examples of material engineering, optoelectronics, cryogenics and superconductivity have been described and it is shown that in engineering education, the coordination between physicist and engineers is a must which results in a faster rate of development in technology for the betterment of mankind.